Multi-analytical study of paint and varnish on a 17th century wooden polychrome antependium - Aida Grga (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The antependium of Saint Michael's altar from the church of Saint Catherine in Osič, Croatia, is a work of the 17th century artist Matej Otoni. As a part of her Master's thesis, Aida Grga carried out a complex analysis of the paint layer (binding medium and pigments) and of the resinous varnish found on the object. Thin layer chromatography, Fourier transform infrared spectroscopy and micro-chemical analysis were used to identify the materials. The investigation was carried out in the Laboratory for Conservation Research at the Arts Academy of the University of Split, under the supervision of PhD Ivica Ljubenkov.